Allogeneic suppressive effects of pregnancy sera on monocytes of responding cells in human mixed lymphocyte reactions. - Nieda, M; Juji, T; Imao, S (The Journal of Clinical Investigation, 1985)
The purified human monocytes of a responding donor preincubated with heat-inactivated serum T1264 or T1295 derived from pregnant women for 30 min at 37 degrees C expressed allogeneic suppressive effects on the proliferative response of the lymphocytes from the same donor in the allogeneic mixed lymphocyte reaction (MLR). The pregnancy serum in our experiments was found not to contain any antibodies to DR and DQ antigens on monocytes of the responding donor. Accordingly, the suppressive effects mediated by monocytes were not based on the blocking of DR and DQ antigens on monocytes of the responding donor by DR and DQ antibodies in the serum. These highly reproducible allogeneic suppressive effects by monocytes of the responding donor were demonstrated in the MLR specific for DRw9-positive stimulating cells, whereas no inhibition was seen in the cultures with other stimulating cells of different DR phenotypes. Additionally, these suppressive effects appeared on the monocytes of a DR2-positive responding donor, but not on the monocytes of a DR2-negative responding donor. These suppressive effects were abolished when the absorbed pregnancy serum by monocytes of the DR2-positive responding donor was used. In this suppression phenomenon that we discovered, monocytes of the responding donor appear to act as regulatory cells on the proliferative response of the allogeneic MLR. This regulatory function of monocytes could be expressed through the specific molecules distinct from DR and DQ determinants on monocytes in cooperation with antibodies (IgG class) in the pregnancy serum.